Depositional environments of the Upper Triassic Snadd Formation on the Loppa High, SW Barents Sea - Johansen, Stian André (UiT The Arctic University of Norway, 2016)
This thesis has focused on the depositional environments of the Upper Triassic Snadd Formation. This formation covers the time-period Ladinian to early Norian with multiple marine regressions and transgressions, resulting in depositional environments ranging from offshore marine shelf to a coastal plain. A 3D seismic dataset and its correlating well have been studied and a refined seismic stratigraphic framework for the Snadd Formation is proposed. The area of investigation is located at the border between the Loppa High, the Bjarmeland Platform and the Hammerfest Basin. The study defines five time-stratigraphic units within the formation, bounded by regional flooding surfaces. Depositional features observed on seismic data, demonstrate distinct depositional environments within each unit. This thesis show that a marine setting dominates the lower units (Ladinian to middle Carnian), with three shorter periods of marine regressions exposing the study area to marginal marine and coastal plain processes. In the upper units (middle Carnian to early Norian), a marine regression shifts the dominating environment from marine to a coastal plain. The deposition of the Snadd Formation ends by a marine transgression, known as the early Norian flooding event.